2013
DOI: 10.1111/jai.12313
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of the endangered ripon barbel,Barbus altianalis(Boulenger, 1900) in Lake Victoria catchment, Kenya based on mitochondrial DNA sequences

Abstract: Summary Approximately 850 bp of the mitochondrial control region was used to assess the genetic diversity, population structure and demographic expansion of the endangered cyprinid Barbus altianalis, a species known to be potamodramous in the Lake Victoria drainage system. The 196 samples taken from the four main rivers draining the Lake Victoria catchment (Nzoia, Yala, Nyando and Sondu–Miriu) yielded 49 mitochondrial DNA haplotypes; 83.7% thereof were private haplotypes restricted to particular rivers. The ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
11
3
Order By: Relevance
“…8), representing five localities. The lack of Cytb diversity among our L. altianalis specimens sharply contrasts with a previous study of this species in this area that reports high haplotype diversity for the mitochondrial control region(Chemoiwa et al (2013). Although our phylogenetic analyses provide little resolution within Labeobarbus, they suggest that our L.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…8), representing five localities. The lack of Cytb diversity among our L. altianalis specimens sharply contrasts with a previous study of this species in this area that reports high haplotype diversity for the mitochondrial control region(Chemoiwa et al (2013). Although our phylogenetic analyses provide little resolution within Labeobarbus, they suggest that our L.…”
contrasting
confidence: 99%
“…This species has historically constituted an important fishery in this region (Whitehead, 1959), but overfishing has severely decimated its populations (Ochumba and Many Ala, 1992). Genetic diversity for this species in the Kenyan LVD has been studied with the mitochondrial control region, which revealed some population structure (Chemoiwa et al, 2013). Muwanika et al (2012) Manuscript to be reviewed sequences from this species in the Kenyan LVD will allow examination of differences among the populations from both countries.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-modal and more ragged distributions are a signature for more stable populations (Rogers & Harpending, 1992), reported in a number of fish taxa including Labeobarbus spp. Rüppell 1835 (Muwanika et al, 2012), Barbus altianalis (Boulenger 1900) (Chemoiwa et al, 2013) and C. batrachus (Lee & Sulaiman, 2015). LKG, however, showed a uni-modal and less ragged distribution, while LNG had a multi-modal and more ragged distribution, suggesting a recent population expansion in LKG, while LNG was a stable population.…”
Section: E M O G R a P H I C E X Pa N S I O Nmentioning
confidence: 99%
“…Naturally small and isolated, satellite lakes have long been recognized as functional refugia for indigenous fish species (Kaufman & Ochumba, ; Kaufman et al , ), whose survival in the main lake is severely threatened or may be extirpated altogether, due to anthropogenic effects. The loss of ichthyofaunal biodiversity in the Lake Victoria basin has called for an urgent need to identify and conserve the remaining populations, including the genetic diversity they contain, as well as their habitats (Kaufman et al , ; Ojwang et al , ; Chemoiwa et al , ). In their study, Barasa et al () reported no significant differentiation between Lakes Victoria and Kanyaboli populations of C. gariepinus , but six private haplotypes were inferred in the Lake Kanyaboli population.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of two populations of many riverine species in River Sondu-Miriu has been reported [18]. Studies on trophic ecology [19] and current molecular studies [20] suggest the existence of non-migratory Barbus altianalis populations within the Lake Victoria catchment. It is not clear whether such changes from potamodromous to stationary behavior has been accompanied by morphological changes among populations of the species.…”
Section: Introductionmentioning
confidence: 99%